Sea Anemone Toxins: A Structural Overview - Bruno Madio; Glenn F. King; Eivind A. B. Undheim (Marine Drugs, 2019)
Sea anemones produce venoms of exceptional molecular diversity, with at least 17 different molecular scaffolds reported to date. These venom components have traditionally been classified according to pharmacological activity and amino acid sequence. However, this classification system suffers from vulnerabilities due to functional convergence and functional promiscuity. Furthermore, for most known sea anemone toxins, the exact receptors they target are either unknown, or at best incomplete. In this review, we first provide an overview of the sea anemone venom system and then focus on the venom components. We have organised the venom components by distinguishing firstly between proteins and non-proteinaceous compounds, secondly between enzymes and other proteins without enzymatic activity, then according to the structural scaffold, and finally according to molecular target.